Structure Flexibility of Alpha-galactosidase from a Marine Psychrophilic Yeast, Glaciozyma antarctica PI12 - Shuhaila Mat-Sharani; Reyad Al Moheer; Farah-Diba Abu-Bakar; Abdul-Munir Abdul-Murad; Nor-Muhammad Mahadi (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2022)
Factors that contribute to maintaining the flexibility or stability of an enzyme structure may depend on the composition of each amino acid with different characteristics, providing a purpose and bonding features within the structure. Based on this assumption, a study using homology modeling and a comparative study to observe different structure behaviors of an enzyme at an extremely low temperature (psychrophile) against temperate (mesophile) and high temperature (thermophile) was performed. The subject, a-galactosidase from Glaciozyma antarctica as a marine psychrophilic candidate was chosen against a-galactosidase from Trichoderma reesei (mesophile) and Ramsonia emersonii (thermophile). This enzyme catalyzes the hydrolysis of a-1-6 linked terminal galactosyl residues which can be found in a wide range of the organism. The ability of G. antarctica to grow in extremely cold temperatures rendered the question that the enzyme must have special characteristics to adapt to the cold condition. Based on the homology modeling and molecular dynamics study, a comparison of the structure of G. antarctica a-galactosidase enzymes with its homolog from the mesophilic and thermophilic fungi showed that G. antarctica a-galactosidase enzyme confers its flexibility by the increased number of small amino acids with reduced charges, more loops, a fewer number of hydrogen and disulfide bonds in its structure. Furthermore, a-galactosidase has potential for commercialization in bleach paper and the baking industry also a treatment for bloating and Fabry disease.